Light-assisted hydrovolt self-energized sensor for detecting microcystic toxins and preparation method and application of light-assisted hydrovolt self-energized sensor

By modifying Zr-MOF/PEDOT composite materials and aptamers on functional glass materials, the photohydrovoltage self-energy sensor is constructed, which solves the problems of cumbersome and high cost of MC-RR detection in the prior art, and achieves fast, accurate and low-cost MC-RR detection.

CN119738458AActive Publication Date: 2025-04-01CHANGZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411807015.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-01
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The prior art methods used to detect microcystis toxin MC-RR have problems such as cumbersome detection process, complicated sample preprocessing, and expensive instruments, and lack fast, accurate and cost-effective detection methods.

Method used

Zr-MOF/PEDOT composite material is used as the power generation material, combined with aptamer (apta) that specifically recognizes the function, and a photohydrovolt self-energy sensor is constructed to realize quantitative detection of MC-RR.

Benefits of technology

Fast, accurate and low-cost MC-RR detection is achieved, with high sensitivity and wide linear range, with a detection limit of 1.01×10-12 M.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119738458A_ABST
    Figure CN119738458A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrochemical detection, and particularly relates to a photo-assisted water-borne self-energized sensor for microcystic toxin detection and a preparation method of the photo-assisted water-borne self-energized sensor for microcystic toxin detection, a water-borne generator is prepared by taking a glass substrate as a substrate, taking copper foil adhesive tapes as positive and negative electrodes and taking a Zr-MOF / PEDOT composite material as a power generation material, and an MC-RR aptamer is assembled to construct the water-borne self-energized sensor. According to the photovoltaic self-energized sensor, the generated electric output is remarkably improved under light assistance, the capacitor is combined into the photovoltaic self-energized sensor, and the capacitor remarkably amplifies the generated electric output through the charging-discharging process within dozens of seconds to several minutes. According to the invention, the application of Zr-MOF and PEDOT in water evaporation induced power generation is widened, a new strategy is provided for electrochemical detection, and the constructed photo-assisted hydrovolt self-energized sensor has the advantages of wide detection range, high sensitivity, low detection limit and low detection cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical detection, and specifically relates to a photo-assisted hydrovoltaic self-powered sensor for detecting microcystin and its preparation method, and more specifically, relates to a Zr-MOF / PEDOT composite material as a substrate material, an aptamer (apta) with a specific recognition function as a recognition unit, which is co-modified on the coating surface of a functional glass material, and apta / Zr-MOF / PEDOT / glass is used to form a photo-assisted hydrovoltaic self-powered sensor, and an electrochemical analysis method for quantitatively detecting microcystin MC-RR in wastewater. . Background Art

[0002] Due to climate change and eutrophication, toxic cyanobacteria (blue-green algae) blooms are increasing worldwide, and microcystins (MCs) produced by cyanobacteria pose a great threat to public health. By specifically binding to protein phosphatases 1 and 2A in the liver, MCs inhibit the functions of these two key enzymes in cell regulation, so long-term accumulation in the human body may lead to a high incidence of primary liver cancer. Among the various isomers of MCs, MC-RR has attracted much attention due to its toxicity and frequent occurrence. Therefore, rapid detection of MCs in essential products such as fish, shellfish, vegetables and algae dietary supplements is particularly important for human health. Current methods for detecting MC-RR include liquid chromatography, protein phosphatase inhibition test, capillary electrophoresis, etc. However, these methods are limited by many factors, such as cumbersome detection process, time-consuming and complex sample pretreatment, and expensive instruments. Therefore, there is an urgent need to develop a rapid, accurate and cost-effective method.

[0003] Hydrovoltaic sensors can generate electricity directly through the interaction between nanostructured materials and water, so they are sustainable, spontaneous, ubiquitous, and pollution-free. They are an environmentally friendly, emission-free strategy that can generate electricity in the absence of light conditions. Light assistance can increase the current response, making the sensor more sensitive. Metal-organic frameworks (MOFs), as a new type of porous crystalline materials, are constructed by alternating inorganic secondary structural units and organic linkers. The high surface area, ideal porosity, and good stability of Zr-MOF are conducive to the construction of hydrovoltaic sensors. Poly (3,4-ethyl-ethylenedioxythiophene) (PEDOT) is a well-known conductive polymer that can accelerate electron transfer and enhance conductivity due to its high conductivity and stable electrical properties. At present, there are no reports on the construction of light-assisted hydrovoltaic power generation devices using Zr-MOF and PEDOT. Summary of the invention

[0004] The present invention aims to provide a photo-assisted hydrovoltaic self-powered sensor and its preparation method and application. The sensor has a simple preparation process, low cost, high sensitivity, and can achieve the purpose of rapid quantitative detection of MC-RR.

[0005] One of the purposes of the present invention is to provide a photo-assisted hydrovoltaic self-powered sensor, which includes a Zr-MOF / PEDOT composite material as a power generation material, an aptamer (apta) with a specific recognition function as a recognition unit, which are jointly modified on the coating surface of a functional glass material to form an apta / Zr-MOF / PEDOT / glass photo-assisted hydrovoltaic self-powered sensor.

[0006] The second object of the present invention is to provide a method for preparing the above-mentioned photo-assisted hydrovoltaic self-powered sensor, and the specific steps are as follows: (1) Preparation of Zr-MOF / PEDOT composite materials: Zr-MOF and PEDOT were uniformly dispersed in anhydrous ethanol and deionized water with a volume ratio of 1:1 to prepare a suspension, thereby obtaining a uniform Zr-MOF / PEDOT composite material suspension.

[0007] (2) Constructing a hydrovoltaic battery: The glass substrate was cleaned in acetone, ethanol and ultrapure water for 30 min respectively. With glass as the substrate and copper foil tape as the electrode, an "I"-shaped upper electrode and an "L"-shaped lower electrode were pasted. The Zr-MOF / PEDOT composite material suspension was dripped between the upper and lower electrodes with a pipette gun to evenly cover the two electrodes. Finally, the prepared device was placed in a 60 ℃ vacuum drying oven to dry.

[0008] (3) Preparation of sensors A certain concentration of MC-RR aptamer is dripped onto the surface of the hydrovoltaic battery power generation material prepared in step (2), and dried naturally at room temperature to obtain a photo-assisted hydrovoltaic self-powered aptamer sensor that selectively recognizes MC-RR.

[0009] Among them, Zr-MOF was prepared by the following method: 5, 10, 15, 20-tetrahydro (4-carboxyphenyl) porphyrin (H2TCPP), zirconium chloride (ZrCl4) and benzoic acid (BA) were added to N, N-dimethylformamide (DMF). After that, H2O was added as a regulator to make a dark green solution. The resulting solution was transferred to a polytetrafluoroethylene liner and hydrothermally reacted in an oven at a temperature of 100-140 °C and a reaction time of 20-28 h. After cooling to room temperature, the resulting precipitate was washed with DMF and filtered, and then soaked in ethanol for 2 days. During this period, the solvent was exchanged and refreshed once every 6 hours. Finally, the precipitate was filtered and heated and dried in a vacuum to obtain purple crystals. The mass ratio of H2TCPP, ZrCl4, and BA was 2-3:3-4:125-145.

[0010] Among them, PEDOT is prepared by the following method: 3,4-ethylenedioxythiophene (EDOT) is slowly dispersed in an aqueous solution of ammonium persulfate, stirred continuously for 2-3 days, centrifuged to obtain a black crude product, washed, and vacuum freeze-dried to obtain PEDOT. The mass ratio of EDOT to ammonium persulfate is 18-22:140-143.

[0011] As one of the preferred technical solutions for the preparation method of the above-mentioned photo-assisted hydrovoltaic self-powered sensor, in the step (1), the concentration of the composite material suspension is 10 mg / ml, and the ultrasonic dispersion is performed for 4 to 8 hours.

[0012] As one of the preferred technical solutions for the preparation method of the above-mentioned photo-assisted hydrovoltaic self-powered sensor, wherein, in the step (1), the mass percentage of Zr-MOF in Zr-MOF / PEDOT is 40-50%.

[0013] As one of the preferred technical solutions for the preparation method of the above-mentioned photo-assisted hydrovoltaic self-powered sensor, in the step (2), the drop coating amount is 60-100 μL / cm 2 In some embodiments of the present invention, the drop coating area is 2.0*3.0cm 2 , the coating volume is 400~600 μL.

[0014] As one of the preferred technical solutions for the preparation method of the above-mentioned photo-assisted hydrovoltaic self-powered sensor, in the step (3), the concentration of the MC-RR aptamer is 1 μM, and the amount of the drop is 3-4 μL / cm 2 .

[0015] The application of the self-powered sensor in the photoelectrochemical detection of MC-RR, the specific sequence of the MC-RR aptamer nucleotide is as follows: Aptamer: 5′-CAG CTC AGA AGC TTG ATC CTA CTG CCC TTC AAT GTT CAC TCC TGTTTC CTG ATC TTT GTC GAC TCG AAG TCG TGC ATC TG-3′.

[0016] The third object of the present invention is to provide the application of the above-mentioned photo-assisted hydrovoltaic self-powered sensor in the detection of microcystin (MC-RR).

[0017] The specific detection method includes the following steps: S1, preparing microcystin MC-RR with different concentrations; Accurately weigh a certain amount of MC-RR and dilute it step by step with deionized water to obtain a series of microcystin standard solutions with different concentrations ranging from 1.0×10-11 mol / L~1.0×10 -8 mol / L; S2. Drawing of standard curve: A series of MC-RR standard solutions with known concentrations were selected and drop-coated on the surface of the prepared hydrovoltaic battery power generation material and dried naturally at room temperature; The upper and lower electrodes of copper foil tape were used as the positive and negative electrodes of the electrochemical test, Zr-MOF / PEDOT composite materials were used as power generation materials, and MC-RR aptamers were assembled to form a hydrovoltaic self-powered system. Deionized water was used as the electrolyte, the xenon lamp light source current was controlled to be 20 A, and the horizontal distance from the light source outlet to the glass substrate was 12 cm. The instantaneous current of charging for 100 s was measured at a test potential of 0 V, and a series of concentration-short-circuit current correspondences were obtained, and then the standard curve of MC-RR was obtained. The linear relationship between the short-circuit current intensity after adding MC-RR and the logarithm of MC-RR concentration was established, and the corresponding linear regression equation was obtained. S3. Actual sample testing: The actual sample is pretreated before detection, and then the pH value is adjusted, and the calculation is performed according to the linear regression equation in the above step S2.

[0018] Preferably, in step S3, the incubation reaction time of the photo-assisted hydrovoltaic self-powered sensor is 20 min.

[0019] The minimum detection limit of the MC-RR solution concentration detected by the sensor is 1.01×10 -12 M.

[0020] Compared with the prior art, the light-assisted hydrovoltaic self-powered aptamer sensor of the present invention has the following beneficial effects: (1) The present invention uses Zr-MOF / PEDOT composite materials as power generation materials to make hydrovoltaic devices. Ordinary glass is used as the substrate material. Zr-MOF is a new type of crystalline porous material with good hydrovoltaic properties, such as high porosity and high surface area. PEDOT is used to enhance the photoelectric response and ion transport, and is used as a local heater to enhance carrier separation and accelerate reaction kinetics. In the preparation of the photo-assisted hydrovoltaic self-powered sensor, light assistance significantly improves the current signal, and the addition of the aptamer enables the sensor to specifically detect MC-RR.

[0021] (2) Compared with traditional detection methods, the aqueous electrochemical detection method proposed in the present invention has the characteristics of simple and flexible operation, simple instrumentation, high sensitivity, wide linear range, low detection limit and low detection cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The present invention will be further described below with reference to the accompanying drawings and examples.

[0023] Figure 1 It is a schematic diagram of the preparation of the sensor and the detection of MC-RR in the present invention.

[0024] Figure 2 It is the current signal measured by the battery with different proportions of composite material added.

[0025] Figure 3 This is a comparison chart of the Zr-MOF / PEDOT composite material before and after using a capacitor to amplify the current signal.

[0026] Figure 4 This is a short-circuit current diagram of the self-powered sensor in Example 2 corresponding to the addition of different concentrations of MC-RR.

[0027] Figure 5 It is the standard curve of the short-circuit current after adding MC-RR in Example 2 and the logarithm of the MC-RR concentration. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below with reference to the embodiments.

[0029] like Figure 1 As shown, a method for preparing a light-assisted hydrovoltaic self-powered sensor and its application in MC-RR detection, a hydrovoltaic generator is prepared using a Zr-MOF / PEDOT composite material as a power generation material to form a self-powered system, and an MC-RR aptamer is assembled to achieve specific detection of MC-RR. Example 1

[0030] Compare the effects of Zr-MOF / PEDOT composites with different mass ratios on the hydrovoltaic performance of the sensor.

[0031] (1) Preparation of Zr-MOF; 50 mg of 5,10,15,20-tetrahydro(4-carboxyphenyl)porphyrin (H2TCPP), 70 mg of zirconium chloride (ZrCl4), and 2700 mg of benzoic acid (BA) were added to 8 mL of N,N-dimethylformamide (DMF). After that, 1000 μL of H2O was added as a regulator to make a dark green solution. The resulting solution was transferred to a 25 ml Pyrex vial and heated in an oven at 120 °C for 24 h. After cooling to room temperature, the resulting precipitate was washed with DMF and filtered 3 times, and then soaked in ethanol for 2 days. During this period, the solvent was changed every 6 hours. Finally, the precipitate was filtered and heated in a vacuum at 80 °C for 12 h, and then purple crystals were obtained.

[0032] (2) Preparation of PEDOT; 0.203 g of 3,4-ethyl-ethylenedioxythiophene (EDOT) was slowly dispersed in 20 mL of ammonium persulfate aqueous solution (0.31 M) and stirred for 3 days; the black crude product was obtained by centrifugation. It was then washed with ultrapure water to remove excess oxidant, and then unreacted oligomers and monomers were removed with methanol (20 mL) and acetone (3 mL), and dried in a vacuum freeze dryer.

[0033] (3) Preparation of Zr-MOF / PEDOT composite materials with different proportions: Aqueous batteries were prepared using Zr-MOF / PEDOT composite materials in different ratios (3:1, 3:2, 1:1, 2:3, 1:3). The specific amounts of Zr-MOF:PEDOT in 2 ml of solvent (anhydrous ethanol and deionized water with a volume ratio of 1:1) were 15 mg:5 mg, 12 mg:8 mg, 10 mg:10 mg, 8 mg:12 mg, 5 mg:15 mg, respectively. Ultrasonic dispersion was performed for 5 hours to obtain a uniform Zr-MOF / PEDOT composite suspension with a suspension concentration of 10 mg / mL.

[0034] (4) Constructing a hydrovoltaic battery: The glass substrate was cleaned in acetone, ethanol and ultrapure water for 30 min respectively. With glass as the substrate and copper foil tape as the electrode, a "one" upper electrode and an "L"-shaped lower electrode were pasted. Zr-MOF / PEDOT composite suspension material was dripped between the upper and lower electrodes with a pipette gun to evenly cover the space between the two electrodes (about 2×3 cm). Finally, the prepared device was placed in a vacuum drying oven at 60°C for drying.

[0035] Hydrovoltaic performance test: The upper and lower electrodes of copper foil tape were used as the positive and negative electrodes of the electrochemical test, and the Zr-MOF / PEDOT composite material was used as the power generation material to form a hydrovoltaic self-powered system. Deionized water was used as the electrolyte, the xenon lamp light source current was controlled to be 20 A, and the horizontal distance from the light source outlet to the glass substrate was 12 cm. The short-circuit current response value was measured at a test potential of 0 V.

[0036] Depend on Figure 2 It can be seen that as the proportion of PEDOT increases, the short-circuit current continues to increase. When the mass ratio of Zr-MOF / PEDOT is 1:1, the short-circuit current is the largest. Therefore, the optimal ratio of Zr-MOF / PEDOT composite material is 1:1.

[0037] Figure 3This is a comparison of the Zr-MOF / PEDOT (1:1) composite material before and after using a capacitor to amplify the current signal. The hydrovoltaic performance after capacitor amplification is the instantaneous current measured after charging for 100 s under the same conditions. It can be seen that the hydrovoltaic performance after amplification is stronger, which can effectively improve the sensitivity of the constructed sensor. Example 2

[0038] A method for constructing a photo-assisted hydrovoltaic self-powered sensor and its application in detecting microcystin, comprising the following steps: (1) Preparation of Zr-MOF: Same as Example 1.

[0039] (2) Preparation of PEDOT: Same as Example 1.

[0040] (3) Preparation of Zr-MOF / PEDOT composite materials: 20 mg of Zr-MOF and 20 mg of PEDOT were added to a 5 ml centrifuge tube, and anhydrous ethanol and deionized water in a volume ratio of 1:1 were added to prepare a 10 mg / mL suspension, and ultrasonic dispersion was performed for 5 hours to obtain a uniform Zr-MOF / PEDOT composite suspension material.

[0041] (4) Constructing a hydrovoltaic battery: The glass substrate was cleaned in acetone, ethanol and ultrapure water for 30 min respectively. With glass as the substrate and copper foil tape as the electrode, a "one" upper electrode and an "L"-shaped lower electrode were pasted. Zr-MOF / PEDOT composite suspension material was dripped between the upper and lower electrodes with a pipette gun to evenly cover the space between the two electrodes (about 2×3 cm). Finally, the prepared device was placed in a vacuum drying oven at 60°C for drying.

[0042] (5) Preparation of sensors 20 μL of 1 μM MC-RR aptamer was dripped onto the surface of the hydrovoltaic battery power generation material prepared in step (4), and dried naturally at room temperature to obtain an aptamer sensor that selectively recognizes MC-RR.

[0043] The aptamer sequences of the above sensors are as follows: Aptamer: 5′-CAG CTC AGA AGC TTG ATC CTACTG CCC TTC AAT GTT CAC TCC TGT TTC CTG ATC TTT GTC GAC TCG AAG TCG TGC ATCTG-3′.

[0044] (6) Drawing of standard curve: Prepare the standard solution of MC-RR: dissolve MC-RR in 10 ml of deionized water, and then dilute it step by step with deionized water to obtain a series of MC-RR standard solutions with different concentrations; In the photo-assisted hydrovoltaic self-powered sensor, the upper and lower electrodes of copper foil tape are used as the positive and negative electrodes of the electrochemical test, the Zr-MOF / PEDOT composite material is used as the power generation material, and the MC-RR aptamer is assembled to form a hydrovoltaic self-powered system. The incubation time of the self-powered aptamer sensor is 20 min, deionized water is used as the electrolyte, the xenon lamp light source current is controlled to be 20 A, and the horizontal distance from the light source outlet to the glass substrate is 12 cm. The instantaneous current of charging for 100s is measured at a test potential of 0 V, such as Figure 4 As shown in the figure, the concentration of MC-RR is as follows from top to bottom (a→g): 1.0×10 -11 mol / L、5.0×10 -10 mol / L、1.0×10 -10 mol / L、5.0×10 -9 mol / L、1.0×10 -9 mol / L、5.0×10 -8 mol / L、1.0×10 -8 mol / L.

[0045] The electrodes modified with different concentrations of MC-RR were used as working electrodes, where the concentrations of MC-RR were (1.0×10 -11 mol / L、5.0×10 -10 mol / L、1.0×10 -10 mol / L、5.0×10 -9 mol / L、1.0×10 -9 mol / L、5.0×10 -8 mol / L、1.0×10 -8 mol / L), deionized water was used as the electrolyte, the xenon lamp source current was selected to be 20 A, the horizontal distance from the light source outlet to the glass substrate was 12 cm, and the response value of its electric power was measured at a test potential of 0 V; then the Figure 5 The linear relationship between the logarithmic value of the concentration of MC-RR and the short-circuit current is shown in Figure 1. The correlation coefficient (R) is 0.97858, and the detection range of the linear regression equation is 1.0×10 -11 -1.0×10 -8 mol / L, the minimum detection limit is 1.01×10 -12 mol / L.

[0046] (7) Sample testing A certain amount of wastewater after impurities removal was used to prepare MC-RR solution for photoelectrochemical detection. The concentration of MC-RR in the sample to be tested was calculated according to the regression equation corresponding to the above step (6). The results are listed in Table 1.

[0047] Table 1 Determination results of MC-RR in water samples .

[0048] As shown in Table 1, the sample was tested three times in parallel, the relative standard deviation was less than 5%, and the spike recovery ranged from 94% to 102%. The present invention can be used to detect MC-RR in wastewater.

[0049] The above described ideal embodiments of the present invention are for inspiration. Through the above description, relevant personnel can make various changes and modifications within the scope of the technical concept of the present invention. The technical scope of the present invention is not limited to the contents of the specification.

Claims

1. A photo-assisted hydrovoltaic self-powered sensor for MC-RR detection, characterized in that: The photo-assisted hydrovoltaic self-powered sensor includes a Zr-MOF / PEDOT composite material as a power generation material and an aptamer with a specific recognition function as a recognition unit, which are jointly modified on the surface of a functional glass to form an apta / Zr-MOF / PEDOT / glass-based photo-assisted hydrovoltaic self-powered sensor.

2. A method for preparing a photo-assisted hydrovoltaic self-powered sensor for MC-RR detection as claimed in claim 1, characterized in that: The method comprises the following preparation steps: Step (1), uniformly dispersing Zr-MOF and PEDOT in anhydrous ethanol and deionized water in a volume ratio of 1:1 to obtain a uniformly dispersed Zr-MOF / PEDOT composite material suspension; the concentration of the Zr-MOF / PEDOT composite material in the suspension is 10 mg / ml; Step (2), using pre-cleaned glass as a substrate and copper foil tape as electrodes, pasting them into an "I"-shaped upper electrode and an "L"-shaped lower electrode, dripping a Zr-MOF / PEDOT composite material suspension between the upper and lower electrodes to evenly spread the suspension between the two electrodes, and drying, thereby obtaining a photo-assisted hydrovoltaic cell; Step (3), adding MC-RR aptamer to the surface of the hydrovoltaic battery power generation material prepared in step (2), and drying naturally at room temperature to obtain a light-assisted hydrovoltaic self-powered sensor for MC-RR detection; the MC-RR aptamer sequence is: 5'-CAG CTC AGAAGC TTG ATC CTA CTG CCC TTC AAT GTT CAC TCC TGT TTC CTG ATC TTT GTC GAC TCGAAG TCG TGC ATC TG-3'.

3. The method for preparing the photo-assisted hydrovoltaic self-powered sensor for MC-RR detection according to claim 2, characterized in that: In step (1), the mass percentage of Zr-MOF in the Zr-MOF / PEDOT composite material is 40-50%.

4. The method for preparing the photo-assisted hydrovoltaic self-powered sensor for MC-RR detection according to claim 2, characterized in that: In step (2), the drop coating amount of the Zr-MOF / PEDOT composite suspension is 60-100 μL / cm 2 .

5. The method for preparing the photo-assisted hydrovoltaic self-powered sensor for MC-RR detection according to claim 2, characterized in that: In step (3), the concentration of MC-RR aptamer was 1 μmol / L, and the amount added was about 3-4 μL / cm 2 .

6. The method for preparing the photo-assisted hydrovoltaic self-powered sensor for MC-RR detection according to claim 2, characterized in that: In step (1), Zr-MOF is prepared by the following method: adding 5,10,15,20-tetrahydro(4-carboxyphenyl)porphyrin, zirconium tetrachloride and benzoic acid to NN-dimethylformamide; adding H2O as a regulator to prepare a solution; hydrothermally reacting the obtained solution at 100-140°C for 20-28 hours; after cooling to room temperature, collecting the precipitate, washing, filtering, solvent exchange, and drying to obtain; wherein the mass ratio of 5,10,15,20-tetrahydro(4-carboxyphenyl)porphyrin, zirconium tetrachloride and benzoic acid is 2-3:3-4:125-145.

7. The method for preparing the photo-assisted hydrovoltaic self-powered sensor for MC-RR detection according to claim 2, characterized in that: In step (1), PEDOT is prepared by the following method: 3,4-ethylenedioxythiophene is slowly dispersed in an aqueous solution of ammonium persulfate, stirred continuously for 2-3 days, centrifuged, washed, and vacuum freeze-dried to obtain the obtained product; wherein the mass ratio of 3,4-ethylenedioxythiophene to ammonium persulfate is 18-22:140-143.

8. An application of the photo-assisted hydrovoltaic self-powered sensor for MC-RR detection as claimed in claim 1, characterized in that: Deionized water was used as the electrolyte, the xenon lamp light source current was controlled to be 20 A, and the horizontal distance from the light source outlet to the glass substrate was 12 cm. The instantaneous current of charging for 100 s was measured at a test potential of 0 V, and the short-circuit current intensity of the photo-assisted hydrovoltaic self-powered sensor described in claim 1 before and after combining with the sample to be tested was obtained. The concentration of MC-RR in the sample to be tested was calculated according to the linear regression equation of the standard curve.

9. The use of the photo-assisted hydrovoltaic self-powered sensor for MC-RR detection according to claim 8, characterized in that: The binding time between the sample to be tested and the aptamer is 10-60 min.

10. The use of the photo-assisted hydrovoltaic self-powered sensor for MC-RR detection according to claim 8, characterized in that: The minimum detection limit of the MC-RR solution concentration was 1.01×10 -12 mol / L.

Citation Information

Patent Citations

  • Method for detecting acetamiprid by using Cu-MOF labeled DNA adapter sensor

    CN107525834A

  • Organic photoelectrochemical transistor sensor for cortisol detection and preparation method and detection method thereof

    CN116500112A

  • Construction method of integrated organic photoelectrochemical transistor sensor for detecting pesticide isocarbophos

    CN117420190A

  • Photo-assisted hydrovolt self-energized sensor and preparation method and application thereof

    CN117517423A

  • Metal-organic frameworks as ion-to-electron transducers and detectors

    US20210164930A1